A developmental and energetic basis linking larval oyster shell formation to acidification sensitivity. Issue 10 (29th May 2013) - Waldbusser, George G.; Brunner, Elizabeth L.; Haley, Brian A.; Hales, Burke; Langdon, Christopher J.; Prahl, Frederick G.
Abstract [1] Acidified waters are impacting commercial oyster production in the U.S. Pacific Northwest, and favorable carbonate chemistry conditions are predicted to become less frequent. Within 48 h of fertilization, unshelled Pacific oyster (Crassostrea gigas) larvae precipitate roughly 90% of their body weight as calcium carbonate. We measured stable carbon isotopes in larval shell and tissue and in algal food and seawater dissolved inorganic carbon in a longitudinal study of larval development and growth. Using these data and measured biochemical composition of larvae, we show that sensitivity of initial shell formation to ocean acidification results from diminished ability to isolate calcifying fluid from surrounding seawater, a limited energy budget and a strong kinetic demand for calcium carbonate precipitation. Our results highlight an important link between organism physiology and mineral kinetics in larval bivalves and suggest the consideration of mineral kinetics may improve understanding winners and losers in a high CO2 world.